Homoeopathic Pathogenetic Trial of Catharanthus roseus: A Multicentric, Double-Blind, Randomized, Placebo-Controlled Trial - Mehra, Pritha; Debata, Lipipushpa; Sahoo, Amulya R.; Rajakumar, B. S. J.; Mahajan, Ashish; Arya, Bhopal S. (Homœopathic Links, 2023)
Medicinal plants have a long history of usage in traditional medicine, and Catharanthus roseus L. (G.) Don is one such plant. However, to understand its homoeopathic therapeutic effect, it was important to find the pathogenetic powers by conducting a drug proving trial. To elicit the pathogenetic response of C. roseus in homoeopathic potencies on healthy human provers, a multicenter, randomized, double-blind, placebo-controlled trial was conducted at four centers under the Central Council for Research in Homoeopathy. The proving trial involved 60 relatively healthy provers. All provers were given placebo in the first phase. After randomization, 40 provers in the intervention group were given C. roseus in 6C, 12C, 30C, and 200C potencies in four phases. The control group of 20 provers were administered unmedicated globules in all the phases. A maximum of 12 doses divided into 4 doses/day for 3 days were administered in all phases of the trial. The symptoms and signs manifested during the trial were noted down by the provers, elaborated by the proving masters, and the data were finally processed at the proving-cum-data processing cell of the Council. Among the 40 provers of the verum group, only 15 provers manifested 22 pathogenetic and 10 placebo symptoms, whereas 30 symptoms were reported by 12 provers in the control group. The symptoms have been manifested predominantly in 200C potency. The pathogenetic response elicited during this trial expands the scope of the use of C. roseus and needs to be further validated by a clinical verification study.
Keywords: Catharanthus roseus; double blind; drug proving; homoeopathic pathogenetic trial; homoeopathy; pathogenetic effect; placebo